Perancangan Interior Family Fun Center di Surabaya - Selvy Cahyadi; Hedy Constancia Indrani; Hendy Mulyono (Intra, 2018)
This design is motivated by problems related to the needs and the desire to spend time with family. At this time the need for togetherness becomes important because of the busyness that is passed in big cities like in Surabaya. Family entertainment is one of the most popular destinations for families to spend time with, but there are still many family entertainment places in Surabaya that do not provide facilities that can be used by all family members consisting of toddlers age to the elderly. So Family Fun Center is a family entertainment place that can offer facilities that can be done with all family members by including the concept of universal design, education, togetherness and the nuances of nature combined with technology and equipped with contemporary design style. Thus, it is expected to make Family Fun Center a choice of destination where the main family entertainment destined by the people of Surabaya.